2014
DOI: 10.3892/mmr.2014.2098
|View full text |Cite
|
Sign up to set email alerts
|

ABCG5/8 variants are associated with susceptibility to coronary heart disease

Abstract: ATP-binding cassette sub-family G member 5 (ABCG5) and ABCG8 are members of an ATP-binding cassette transporter superfamily. ABCG5 and ABCG8 variants affected serum levels of cholesterol and were considered as risk factors for coronary heart disease (CHD). The present control study analyzed ABCG5 and ABCG8 variants in a population for association with the risk of CHD. A total of 417 CHD patients and 267 controls were recruited for genotyping of four single nucleotide polymorphisms (SNPs; i.e. i7892T>C in ABCG5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…CHD is a complex disease, involving interactions between environmental and genetic factors (Feng et al, 2014). Previous studies have found that single nucleotide polymorphisms (SNPs), important genomic elements, can affect an individual's genetic susceptibility to various diseases, including CHD Muiya et al, 2014;Wu et al, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…CHD is a complex disease, involving interactions between environmental and genetic factors (Feng et al, 2014). Previous studies have found that single nucleotide polymorphisms (SNPs), important genomic elements, can affect an individual's genetic susceptibility to various diseases, including CHD Muiya et al, 2014;Wu et al, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that individuals carrying the risk genotype for both ABCG8 variants had an increased risk of cardiovascular disease (RR 1.57, 95% CI 1.13–2.18; p = 0.01) and coronary heart disease (RR 1.72, 95% CI 1.23–2.41; p = 0.002). Wu et al ( 41 ) investigated the association between four ABCG5 and ABCG8 SNPs and CAD. Binary logistic regression analysis demonstrated that the homozygous C allele at Thr400LysC>A (rs4148217) resulted in a more than 2-fold greater risk of developing CAD, compared with those who carried the A allele in a dominant model.…”
Section: Discussionmentioning
confidence: 99%
“…ABCG8 (ATP-binding cassette subfamily G member 8) is an instance of a new susceptibility gene for angina pectoris identified by our combined approach. It has been previously reported that ABCG8 variants are risk factors for coronary heart disease 23 . ZC3H4 (zinc finger CCCH domain-containing protein 4) is a candidate gene associated with susceptibility to type 2 diabetes (T2D) identified via the combined approach alone.…”
Section: New Risk Loci Identified In Gwasmentioning
confidence: 99%